Expanded graphene oxide fibers with high strength and increased elongation. Issue 8 (31st January 2019) - Ugale, Ashok D.; Chi, LinLin; Kim, Min-Kyu; Chae, Sudong; Choi, Jae-Young; Yoo, Ji-Beom
Abstract : The increased interplanar distance between the EGO sheets favored the edge-to-edge than basal plane interaction within the fiber, resulting in high mechanical strength (492 MPa) and increased elongation (6.1%). Abstract : We report the role of chemically expanded graphite in the fabrication of high-performance graphene oxide fibers by wet spinning. X-ray diffraction peak showed that the interplanar distance of the expanded graphene oxide (EGO) fiber was more than that of graphene oxide (GO) fiber due to the expanded graphite. X-ray photon spectroscopy analysis revealed that EGO was more oxidized than GO. The hydrogen bonding network and secondary intermolecular interaction made the EGO aqueous solution more stable and crystalline, and it was able to be stretched in the coagulation bath. Morphological analysis showed the excellent alignment and compactness of EGO sheets in the fibers. The increased interplanar distance between the EGO sheets favored the edge-to-edge interaction more than the basal plane interaction within the fiber, thus resulting in high mechanical strength (492 MPa) and increased elongation (6.1%).